Nutritional food and friendly service: a conceptual framework for Toyyib food outlet - Che Noh, Che NurHidayu; Md Dahlal, Norazilawati (AIJR Publisher, 2023)
This paper presents a conceptual framework for toyyib food outlets, focusing on the key aspects of nutritional food and friendly service which employed a qualitative method using secondary data. The availability of nutritious food options and friendly service in food outlets is crucial for promoting healthier choices and enhancing customer satisfaction. Nutritional food involves consuming a balanced diet that provides essential nutrients, considering factors like portion control, food safety, sustainability, and cultural preferences. Friendly service encompasses creating a welcoming environment, delivering attentive customer interactions, and ensuring efficient service. Toyyib food outlets adhere to Islamic principles, emphasizing wholesomeness, cleanliness, and ethical practices. By incorporating these principles, food outlets can offer nutritious and safe food options, prioritize cleanliness and hygiene, and provide courteous and respectful service. This holistic approach promotes healthier food choices, prevents diet-related diseases, and contributes to the overall well-being of individuals and communities.